Challenges and Solutions to Bringing Chimeric Antigen Receptor T-Cell Therapy to Myeloid Malignancies. Issue 2 (March 2021) - Borot, Florence; Mukherjee, Siddhartha; Ali, Abdullah Mahmood
Abstract : Abstract: Myeloid malignancies including myelodysplastic syndromes and acute myeloid leukemia are a group of clonal hematopoietic stem progenitor cell disorders mainly effecting the elderly. Chemotherapeutic approaches improved the outcome in majority of the patients, but it is generally associated with severe toxicities and relapse and does not benefit all the patients. With the success of adoptive cell therapies including chimeric antigen receptor T-cell therapy in treating certain B-cell malignancies, these therapeutic approaches are also being tested for myeloid malignancies, but the preclinical and limited clinical trial data suggest there are significant challenges. The principal hurdle to efficient targeted immunotherapy approaches is the lack of a unique targetable antigen on cancer cells leading to off-target effects including myelosuppression due to depletion of normal myeloid cells. Advanced age of the patients, comorbidities, immunosuppressive bone marrow microenvironment, and cytokine release syndrome are some other challenges that are not unique to myeloid malignancies but pose significant challenge for the successful adaptation of this approach for treatment. In this review, we highlight the challenges and solutions to adopt chimeric antigen receptor T-cell therapies to treat myeloid malignancies.